2014
DOI: 10.1080/10298436.2014.943127
|View full text |Cite
|
Sign up to set email alerts
|

Calculating rutting of some thin flexible pavements from repeated load triaxial test data

Abstract: This paper describes parts of a Nordic pavement performance prediction model study (at the project level of the NordFoU project) where a material performance model, developed at VTT research centre in Finland, has been selected as a mean of calculating the permanently accumulated (plastic) deformation (i.e. rutting) of unbound granular materials (UGMs) in flexible pavements subjected to trafficking. The paper aims to assess the suitability of this VTT model application to Swedish roads comprising thin asphalt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Moisture content can alter the resistance of permanent deformation in unbound granular materials dramatically [13,14]. The repeated load may cause positive pore water pressure to increase in unbound granular layers, which will consequently reduce the effective stress in unbound granular layers, which in turn decreases the stiffness and resistance to permanent deformation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moisture content can alter the resistance of permanent deformation in unbound granular materials dramatically [13,14]. The repeated load may cause positive pore water pressure to increase in unbound granular layers, which will consequently reduce the effective stress in unbound granular layers, which in turn decreases the stiffness and resistance to permanent deformation [15].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the rutting deformation is known to augment with increasing temperature and tire pressure and to be inversely proportional with respect to the subgrade strength. Studies that highlight the importance of the rutting phenomenon in the road pavement are reported in Ahmed and Erlingsson (2013), Darabi et al (2012), Qiao et al (2015), Rahman and Erlingsson (2015), Saevarsdottir and Erlingsson (2015). In some e-road solutions, the insertion of charging devices could lead to stress concentration in the proximity of the devices, resulting in an accelerated, deeper rutting.…”
Section: Introductionmentioning
confidence: 99%
“…(), Qiao et al. (), Rahman and Erlingsson (), Saevarsdottir and Erlingsson (). In some e‐road solutions, the insertion of charging devices could lead to stress concentration in the proximity of the devices, resulting in an accelerated, deeper rutting.…”
Section: Introductionmentioning
confidence: 99%
“…Subsurface failure mechanisms and cumulative strain through the support layers to the subgrade is still not well understood. This is surprising given that previous research has shown that 30 to 70% of surface rutting is generated in the lower granular layers (Qiao et al, 2015). This means that understanding of permanent strain accumulation behaviour is essential for accurate performance prediction (Boulbiband & Collins, 2015).…”
Section: Introductionmentioning
confidence: 97%